PENGARUH IKLAN MULTIVITAMIN TERHADAP KONSUMSI MULTIVITAMIN OLEH MASYARAKAT KABUPATEN TOJO UNA-UNA - Ririen Hardani; Firdawati Amir Parumpu; Farida Abd. Rasul (Universitas Pahlawan, 2022)
In recent years, there have been numerous multivitamin advertising on television, magazines, and other print media. Data from the third quarter of 2013 revealed that advertising purchases in the pharmaceutical business, including medicines, are in the third tier. The research objective was to identify the percentage of Tojo Una-Una Regency people who consume multivitamins, the sources of advertising media that Tojo Una-Una Regency people frequently use as Multivitamin information, and the effect multivitamin advertising has on Tojo Una-Una Regency people's consumption. Purposive sampling was used to select a sample of 100 people in Tojo Una-Una Regency as the sample. The research took place between September and October of 2021. Multiple linear regression analysis was conducted, with SPSS statistics being used. According to the study's findings, 88% of people take multivitamins, whereas 12% never do. With a percentage of 58%, television is the source of advertising media that is frequently used as multivitamin information by the residents of Tojo Una-Una Regency. Concurrently, advertisement factors showed a remarkable effect on behavior consumption, with an F-count of 5.716. Advertising slogans, advertising music, and advertising stars had no significant consequences on consumption with a significant value larger than 0.05. However, story illustration had a crucial effect on multivitamin consumption with a sig value of 0.015. Keyword : advertisement, consumption, multivitamins